Performance of Mhande song-dance: a contextualized and comparative analysis - Rutsate, Jerry (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2008)
This thesis is an investigation of the significance of Mhande song-dance in two performance contexts: the Mutoro ritual of the Karanga and the Chibuku Neshamwari Traditional Dance Competition. In addition, I undertake comparative analysis of the structure of Mhande music in relation to the structure of selected genres of Shona indigenous music. The position of Mhande in the larger context of Shona music is determined through analysis of transcriptions of the rhythmic, melodic and harmonic elements of chizambi mouth bow, karimba mbira, ngororombe panpipes, ngano story songs, game, hunting, war, and love songs. Mhande is an indigenous song-dance performed for the mutoro ceremony, the annual rain ritual of the Karanga. The Mhande repertoire consists of distinctive songs and rhythms used for communicating with the majukwa rain spirits. The rain spirits in turn communicate with God (Mwari) the provider of rain, on behalf of the Karanga. Mhande song-dance is performed exactly the same way in the annual Chibuku Neshamwari Traditional Dance Competitions as in the ritual context of the mutoro ceremony. However, in the context of the Competition, it is used for the expression of joy and as a form of cultural identity. The Competition is a forum in which Karanga songdance traditions such as Mhande, compete with other Shona song-dance traditions such as mbakumba, shangara and chinyambera. I contextualize and analyse Mhande song-dance by using the 'Matonjeni Model', which in terms of Karanga epistemology, is culture specific. This Model is grounded in description, interpretation and analysis; the primary methods in my research process.
Keywords: Karanga (African people) -- Music; Shona (African people) -- Music; Folk music -- Zimbabwe; Music -- Zimbabwe; Folk songs, Shona; Mhande; Dance music -- Zimbabwe